2021
DOI: 10.1017/s0003975621000072
|View full text |Cite
|
Sign up to set email alerts
|

Homophobia and national collective narcissism in populist Poland

Abstract: Opposition to sexual minority rights in Poland is among the highest in the EU. Populist political actors in the country repeatedly scapegoat gays and lesbians, presenting them as a threat to the Polish nation and its shared norms and values, particularly those derived from religion. Building upon previous research which shows how discourse constructing homosexuality as a threat to the nation has been used by social and political actors to legitimize homophobic rhetoric and behaviour, our paper shows whether na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 33 publications
(21 reference statements)
0
17
0
Order By: Relevance
“…Prejudice toward sexual dissenters was measured as a concern that nontraditional women and gay people threaten national identity. This measure was composed of two scales: a scale measuring perception of nontraditional women as a national threat (“Women who do not have children threaten the survival of their nation,” “For the sake of the nation, men should control women,” “Women should ‘respect themselves’ for the good of the nation,” “Women’s equality is a threat to Poland”) and a scale measuring the perception of gay people as a threat to national survival (“Not having children, gays, and lesbians threaten the survival of their nation”; “Homosexuality is a threat to Poland”; “Homosexuality is a Western import”; “Gays do not possess the traits needed for the military defense of the nation”; Mole, Golec de Zavala, & Adraq, 2020). The two measures were strongly, positively correlated in all measurement waves (T1: r (1058) = .63; T2: r (930) = .64; T3: r (892) = .69, all p s < .001).…”
Section: Methodsmentioning
confidence: 99%
“…Prejudice toward sexual dissenters was measured as a concern that nontraditional women and gay people threaten national identity. This measure was composed of two scales: a scale measuring perception of nontraditional women as a national threat (“Women who do not have children threaten the survival of their nation,” “For the sake of the nation, men should control women,” “Women should ‘respect themselves’ for the good of the nation,” “Women’s equality is a threat to Poland”) and a scale measuring the perception of gay people as a threat to national survival (“Not having children, gays, and lesbians threaten the survival of their nation”; “Homosexuality is a threat to Poland”; “Homosexuality is a Western import”; “Gays do not possess the traits needed for the military defense of the nation”; Mole, Golec de Zavala, & Adraq, 2020). The two measures were strongly, positively correlated in all measurement waves (T1: r (1058) = .63; T2: r (930) = .64; T3: r (892) = .69, all p s < .001).…”
Section: Methodsmentioning
confidence: 99%
“…As an individual difference variable, collective narcissism can characterise group members with a relative degree of stability in reference to the same social identity (as indicated by longitudinal studies; Federico et al, 2021;, and across intersecting social identities (as indicated by studies comparing collective narcissism with reference to different social identities; Golec de Zavala & Keenan, 2022b;Mole et al, 2021). However, like group membership salience and ingroup identification (Mullen et al, 1992;Thomas et al, 2020), collective narcissism is higher among members of disadvantaged groups in comparison to members of advantaged groups (Bagci et al, 2021;Golec de Zavala & Keenan, 2022a;Golec de Zavala et al, 2009).…”
Section: Gender Collective Narcissism and Parochial Vicarious Ostracismmentioning
confidence: 99%
“…Further research with the inclusion of a non-binary group would seem to be of particular interest (Scandurra et al, 2019 ). The psychosocial situation of non-binary people should be monitored all the more carefully, as the existence of anti-LGBTI attitudes in Poland, marginalization and stereotypical representation of this social group can still be observed (Chojnicka, 2015 ; Mole et al, 2021 ). Actions for the inclusion of non-binary people are consistent with one of the goals of the UN document Transforming our World: the 2030 Agenda for Sustainable Development (2015), which is to “Promote peaceful and inclusive societies for sustainable development, provide access to justice for all and build effective, accountable and inclusive institutions at all levels”.…”
Section: Limitations and Future Researchmentioning
confidence: 99%